Development of Triticale × Wheat Prebreeding Germplasm With Loci for Slow-Rusting Resistance - Skowrońska, Roksana; Mariańska, Monika; Ulaszewski, Waldemar; Tomkowiak, Agnieszka; Nawracała, Jerzy; Kwiatek, Michał T. (Frontiers in Plant Science, 2020)
There is a growing interest in breeding and production of hexaploid triticale (×Trititcoseale Wittmack ex A. Camus) in European Union and in the World. It is reported, that triticale can be an alternative to wheat (Triticum aestivum L.) for livestock feed production and has a potential to become preferred industrial energy crop. Fungal diseases, mainly leaf and stripe rusts are the limiting factors of triticale growth and yield. Geneticists and breeders are now focusing on accumulation of the major genes for durability of rust resistance. Slow-rusting genes Lr34/Yr18 and Lr46/Yr19 are being exploited in many wheat breeding programs. This type of horizontal resistance is reported to be effective over the space and time. Classical breeding techniques supported by the marker assisted selection (MAS) are the main tools in breeding programs. The aim of this study was to assess the possibility of transfer of slow-rusting genes loci from resistant genotypes of wheat into hexaploid triticale through cross-hybridizations. Amount of 5,094 manual pollinations were conducted between two triticale cultivars Fredro and Twingo and thirty three accessions of common wheat, which were reported as sources of slow-rusting resistance genes. The investigation of the slow-rusting loci transmission was performed using both molecular markers analyses and genomic in situ hybridization. In total, thirty four F1 hybrid plants were obtained and twenty nine of them carried both slow rusting loci. Therefore, these hybrids may be used for triticale pre-breeding program.